Construction of a series of Zn(II) and Cd(II) coordination polymers using a mixed-ligand approach: Structural analysis and photophysical properties. (15th May 2019) - Kirandeep,; Gauri,; Sharma, Ananay; Guda, Ramu; Kumar, Praveen; Kataria, Ramesh; Husain, Ahmad; Kumar, Girijesh
Graphical abstract: A series of coordination polymers, CP1 –CP6, has been solvothermally synthesized using the mixed-ligand (flexible and rigid) approach. Coordination polymers derived from 3-bpna are closely packed and thus do not contain significant SAVs, while those derived from the flexible dpmndi ligand possess SAVs occupied by guest molecules. The conformational orientation along with the coordination mode of the ligands 3-bpna and dpmndi play a crucial role in the generation of a diverse range of topologies inCP1 –CP6 . Photophysical studies reveal that all ofCP1 –CP6 are good fluorescence materials in the solid state. Abstract: A mixed ligand approach has been applied for the synthesis of a series of Zn(II) and Cd(II) coordination polymers, namelyCP1 [Zn(3-bpna)(bdc)·CH3 OH] α, CP2 [Cd(3-bpna)(oba)·DMF·H2 O] α, CP3 [Cd(3-bpna)(5-nipa)·2DMF] α, CP4 [Zn2 (dpmndi)(oba)3 ·4H2 O] α, CP5 [Zn(dpmndi)0.5 (oba)·DMF·DMF·H2 O] α andCP6 [Cd(dpmndi)(bdc)·DMF] α, which are constructed by the reactions of the ligand 3-bpna or dpmndi and Zn(NO3 )2 ·6H2 O or Cd(NO3 )2 ·4H2 O in the presence of different dicarboxylate ligands, specifically terephthalic acid, 4, 4′-oxydibenzoic acid and 5-nitroisophthalic acid, as a co-ligand under solvothermal conditions. These coordination polymers were structurally characterized and display 1D, 2D and 3D network structures. Moreover, their fluorescent behavior was also investigated and the results are found to be very promising.